PENERAPAN KONSEP HARTA DALAM ISLAM PADA KEGIATAN EKONOMI MAHASISWA S1 EKONOMI ISLAM: Studi Kasus di UIN Sjech M. Djamil Djambek Bukittinggi - Subeno, Hadi; Taufiq, Muhammad (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
A person or group of people is generally free to enjoy, spend and/or use their property/wealth without anyone to prevent it as long as the funds obtained are halal. However, private property cannot be absolute, because according to the principles of Islamic law, "the property of a Muslim belongs to others". Spending money on things sometimes puts wants above needs. The resources used are things that can be consumed rather than productive values that lead to charity and habit. Islamic consumerism is a human activity that is beneficial for the benefit of the Ummah, related to the purchase and use of goods and services, which embodies the tenets of Islamic teachings. In Islamic economics, the purpose of consumption is to meet physical and spiritual needs so as to maximize the role of humans as servants of Allah SWT to achieve prosperity or happiness in the world and in the Hereafter (falah). Based on previous researchers' information, the management of student property (consumption) is not in accordance with Islamic consumption law. in relation to purchases. Online store goods, students often do not pay attention to consumption rules according to Islamic teachings.  To reason the study, a type of library research is used with a normative approach method and content analysis whose focal point is the study of manuscripts and texts related to research problems